“Words, words, save our souls…”: letters of hryhorii Bilous - Baran, Yevhen (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
This article explores the life and work of Ukrainian writer and Sixtier Hryhorii Pavlovych Bilous (1940–2011), and presents a selection of his letters addressed to Yevhen Baran.